DISTRIBUSI MITOKONDRIA DAN EKSPRESI BAX PADA HUVEC’s YANG MENGALAMI APOPTOSIS AKIBAT INDUKSI OX-LDL - Riawan, Wibi; Wibowati, Samodrijanti (Jurnal Kedokteran Brawijaya, 2006)
ABSTRACT It had been revealed that endothelial dysfunction which is caused by oxydized LDL is related to TNF Receptor Apoptosis Including Ligand (TRAIL) mechanism. However, there is study to see the involvement of mitochondrial mecanism in Ox-LDL endothelial cells dysfunction. This study was done to see the effect of Ox-LDL treatment on apoptosis of HUVEC’s culture  whether  associated  with  the  distribution  of  mitochondria  or  BAX  expression,  the  main  protein  mitochondria apoptosis mechanism. HUVEC’s culture was divided into two groups: control group and treatment group ( 50 mg/ml Ox-LDL for 24 hours). Doublestaining for DNA fragmented (TUNEL) and BAX expression were done respectively, as well as immunochemistry  using  monoclonal  Ab  of  mitochondria.  In  the  control  group  mitochondria  was  distributed  firmly  on cytoplasma of endothelial cells. In contrast, mitochondria were only found near nuclear membrane cells on treatment group  (this  future  usually  found  on  divided  cells) there  was  also  an  increasing  of  BAX  expression  and  a  mount  of apoptotic cells on treatment group compared with control group. It can be concluded that mitochondria is involved in apoptosis of Ox-LDL endothelial cells in order to serve the abundant energy. Keywords: Mitochondria distribution, Bax expresson, Apoptotic, Ox-LDL